Effect Of Profitability, Leverage, Firm Size On Tax Avoidance : Case study on Banking Companies Listed on the IDX 2023 Period - Gumelar, Aprijal; Susanto, Heri; Sukayat, Harmoko (Institut Bisnis dan Informatika Kesatuan, 2024)
This study certainly aims to be able to test and analyze how much influence profitability, leverage, firm size has on tax avoidance with a case study of banking companies listed on the Indonesian Stock Exchange (IDX) period 2023. This form of research uses a causal associative approach method with a quantitative approach. The data was collected using purposive sampling method (according to certain criteria). The analysis carried out uses quantitative descriptive analysis method, classical assumption test, multiple regression, hypothesis testing, simultaneous test and coefficient of determination. The results of this study are partial or T test shows that profitability and leverage affect tax avoidance. While company size has no effect on tax avoidance. However, together or simultaneously shows that profitability, leverage, firm size have an effect on tax avoidance (case study on banking companies listed on IDX for the period 2023). Keywords: Profitability, leverage, firm size, tax avoidance